The Impact of Obesity on Total Knee Arthroplasty Outcomes: A Systematic Review - Andriessanto Ceelvin Lengkong (Publikasi Indonesia, 2024)
One frequent orthopaedic procedure for treating advanced knee arthritis is total knee arthroplasty, or TKA. Obesity is defined as a body mass index of 30 kg/m2 or greater, and it might have an impact on post-operative problems. Comparing multifactor matched obese and non-obese individuals, we look at the incidence of certain problems, revision rates, and post-TKI care expenses. We predict that patients who are obese will experience worse outcomes than those who are not fat. Obesity was linked to higher rates of medical complications like acute kidney injury, deep vein thrombosis, urinary tract infection, and opioid use, but significantly lower rates of anemia, arrhythmia, cardiac arrest, pneumonia, and transfusion. Surgical complications included wound complications, surgical site infections, need for revision, and higher overall cost of care one year after TKA. Patients who were obese also had far reduced prescription expenditures for treatment. When compared to similar non-obese individuals, the outcomes for obese people were not inherently poorer. However, as obesity is expected to continue rising in prevalence, knowing the problems that might occur after TKA can help inform patients about possible dangers from surgery and direct surgeons in providing care for their patients. Therefore, in order to create new treatments, future research should look at the underlying processes that lead to these issues.